Pengaruh Kesadaran Wajib Pajak Dan Pelayanan Fiskus Terhadap Penerimaan Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan (PBB-P2) Di Kabupaten Buleleng - Saputra, Komang Aryadi; Yasa, I Nyoman Putra (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to determine the effect of taxpayer awareness and tax services on rural and urban land and building tax revenue (PBB-P2). This study uses a quantitative approach using instruments in its measurement and statistical processing. This research was conducted in Buleleng Regency with a population of 238,000 rural and urban land and building taxpayers (PBB-P2). Sampling using purposive sampling in order to obtain a sample of 265 taxpayers. The research data were collected using a questionnaire which was then processed with multiple linear regression analysis with the help of SPSS version 22.The results of the study stated that (1) taxpayer awareness (X1) had a positive and significant effect on PBB-P2 revenue and (2) tax authorities (X2) has a positive and significant effect on PBB-P2 revenue. Abstract This study aims to determine the effect of taxpayer awareness and tax services on rural and urban land and building tax revenue (PBB-P2). This study uses a quantitative approach using instruments in its measurement and statistical processing. This research was conducted in Buleleng Regency with a population of 238,000 rural and urban land and building taxpayers (PBB-P2). Sampling using purposive sampling in order to obtain a sample of 265 taxpayers. The research data were collected using a questionnaire which was then processed with multiple linear regression analysis with the help of SPSS version 22.The results of the study stated that (1) taxpayer awareness (X1) had a positive and significant effect on PBB-P2 revenue and (2) tax authorities (X2) has a positive and significant effect on PBB-P2 revenue.